Relationship between sperm parameters and clinical outcomes of Intra Uterine Insemination (IUI) - Fatemeh Mohammadi; Zohreh Mehdinia; Samaneh Ghasemi; Zahra Zolfaghari; Fatemeh Sadat Amjadi; Mahnaz Ashrafi; Zahra Zandieh (Babol University of Medical Sciences, 2021)
Background: Intrauterine insemination (IUI) is a widely utilized method for treating the infertile couples. The aim of the present study was to determine the pregnancy and abortion rates after IUI and to examine the relationship of sperm parameters with these rates. Methods: This retrospective study was performed on 911 infertile couples undergoing IUI treatment in Shahid Akbarabadi IVF Centre from May 2017 to May 2019. To evaluate the correlation of sperm parameters with the clinical pregnancy and abortion rates, odds ratio (OR) with 95% confidence intervals (CI) was calculated. Results: In this study, the pregnancy rate following IUI was 15.7% (143/911), and among women who achieved pregnancy, the abortion rate was 42.0% (60/143). According to the multiple logistic regression analysis, none of the sperm parameters was associated with the pregnancy rate. Couples with either male or female factor infertility etiologies were more likely to get pregnant than those with unexplained infertility. Regarding the abortion rate, multiple logistic regression analysis revealed that normal sperm count was related to a lower abortion rate (adjusted OR=0.25, 95% CI=0.07-0.91). Conclusion: The present study did not reveal a significant relationship between none of the sperm parameters and pregnancy rate after IUI treatment. However, among women who got pregnant, continuation of the pregnancy was associated with the normal sperm count. Furthermore, analysis of all semen parameters together in comparison to one parameter alone might be more accurate to predict pregnancy or abortion. Further prospective cohort studies with a large number of couples are required.